Effect of sales promotion on cosmetic products buying behaviour among University Malaysia Kelantan students and staffs - Chew, Xue LI; Abd Ghafar, Amir Hasyim; Che Amran, Che Adawiah; Pitchaymuthu, Vijayalechumi (2015)
In today's business world customers are considered to be king. It is important for producers to meet the needs of customers in order to stay competitive. One of the marketing tools that were use in attracting the attention of the customer was sales promotion. The aim of this study was to determine the effect of sales promotion on cosmetic product buying behaviour among University Malaysia Kelantan students and staffs. In the emerging business scenario various promotional techniques are used by marketers. Through this study, an effort has been made to find out the sale promotional tools which were the price discount, free sample and membership card and its impact on customer buying behaviour of cosmetic product. For conducting the research, quantitative research approach was used and questionnaire was distributed to collect the data through simple random sampling 150 respondents from University Malaysia Kelantan students and staffs. There were significant relationship between cosmetic products buying behaviour towards price discount (r=0.561,p<0.01), free sample (r=0.368, p >0.01). The findings of this study would help marketers to understand the types of sales promotion that findings of this study would help marketers to understand the types of sales promotion that significantly influence the cosmetic product buying behaviour of the respondent. Hence, this could help marketers in their marketing planning to become more competitive and can gain profit